Estimation of stature from length of ulna in Maharashtrian population - Avantika Bamne,; Shrikrishna N.Bamne,; Rajveer S.Choursia,; Vineet K.Gohiya, (Universiti Kebangsaan Malaysia, 2015)
Background: Estimation of stature has a significant importance in the field of forensic medicine and anthropometry. Objectives: In this study, an attempt was made to estimate linear regression equation from length of ulna. Materials and Methods: This study was carried out on 200 healthy individuals (100 men and 100 women) of Maharashtrian population, with age ranging from 20 to 25 years, in the Department of Anatomy, Krishna Institutes of Medical Sciences University, Karad, Maharashtra, India. Results : The study showed positive correlation between total height of individuals and length of ulna, which is 0.73 in men and 0.70 in women. Conclusion: The lengths of ulna provide good reliability in estimation of stature in forensic examinations.